Astrocytes and epilepsy - Hubbard, Jacqueline A.; Binder, Devin K.; ScienceDirect eBooks (London, United Kingdom : Academic Press is an imprint of Elsevier, 2016)
"Epilepsy is a devastating group of neurological disorders characterized by periodic and unpredictable seizure activity in the brain. There is a critical need for new drugs and approaches given than at least one-third of all epilepsy patients are not freed of seizures by existing medications and become "medically refractory." Much of epilepsy research has focused on neuronal therapeutic targets, but current antiepileptic drugs often cause severe cognitive, developmental, and behavioral side effects."--Page 4 of cover.
History of astrocytes -- Astrocytes in the mammalian brain -- Gliotransmitters -- Types of epilepsy -- Neuropathology of human epilepsy -- Astrocyte calcium signaling -- Potassium channels -- Water channels -- Glutamate metabolism -- Adenosine metabolism -- Gap junctions -- Blood-brain barrier disruption -- Inflammation -- Therapeutic targets and future directions.
Includes bibliographical references and index.
Online resource; title from PDF title page (ScienceDirect, viewed July 13, 2016).
Elsevier
Keywords: Astrocytes; Epilepsy -- Molecular aspects; MEDICAL / Physiology; SCIENCE / Life Sciences / Human Anatomy & Physiology; Astrocytes; Electronic books